Resistance training presents beneficial effects on bone development of adolescents engaged in swimming but not in impact sports: ABCD Growth Study - Agostinete, Ricardo R. [UNESP]; Werneck, André O; Narciso, Pedro H. [UNESP]; Ubago-Guisado, Esther; Coelho-E-Silva, Manuel J.; Bielemann, Renata M.; Gobbo, Luis Alberto [UNESP]; Lynch, Bruna Turi; Fernandes, Romulo Araújo [UNESP]; Vlachopoulos, Dimitris (Springer Nature, 2024)
BACKGROUND: Sports practice during adolescence is important to enhance bone development, although it may provide different effects depending on the mechanical impact present in the sport. Besides, resistance training (RT) may also induce bone changes directly (via muscle contractions) and indirectly (via myokines). However, there have been no studies analyzing the longitudinal influence of engaging in sport with and without added mechanical load. Thus, this study aims to analyze the combined effects of sports participation and resistance training on areal bone mineral density (aBMD) accrual in adolescent athletes participating in swimming and impact sports for 12-months. METHODS: This was a 12-month longitudinal study. The sample comprised 91 adolescents (21 females) aged 10 to 18 years, engaged in impact sports (basketball, tennis, track & field, baseball and gymnastics, n = 66) and non-impact sport (swimming, n = 25). The sample was divided according to resistance training participation: impact sports only (n = 45), impact sports + resistance training (n = 21), swimming-only (n = 17) and swimming + resistance training (n = 8). aBMD and soft tissues were measured using dual-energy X-ray absorptiometry. Generalized linear models analysis was used for the resistance training (RT) x type of sport interaction in predicting aBMD changes overtime, adjusting for maturation, sex and baseline aBMD. RESULTS: After 12-months, all groups showed a significant increase in aBMD, except for the swimming groups (regardless of resistant training), which showed a significant loss in spine aBMD (-0.045 [-0.085 to -0.004] g/cm2 in swimming-only and - 0.047 [-0.073 to -0.021] g/cm2 in swimming + RT). In comparisons between groups, only swimming + RT group, compared with swimming-only group presented higher upper limbs aBMD (0.096 g/cm2 [0.074 to 0.118] in swimming + RT vs. 0.046 [0.032 to 0.060] g/cm2 in swimming only; p < 0.05) and whole body less head (WBLH) aBMD (0.039 [0.024 to 0.054] g/cm2 in swimming + RT vs. 0.017 [0.007 to 0.027] g/cm2 swimming-only; p < 0.05). CONCLUSION: Despite the significant gain in aBMD in all groups and body sites after 12-months, except for the spine site of swimmers, the results indicate that participation in RT seems to improve aBMD accrual in swimmers at the upper limbs and WBLH.
Keywords: Adolescence; Bone mineral density; Bone tissue; Physical activity; Sport participation